Nutritional Status and Prevalence of Angular Cheilitis on Children in Jember Agroindustrial Environment - Dyah Setyorini; Sulistiyani Sulistiyani; Risma Nur Baiti; Niken Probosari; Roedy Budi Rahardjo; Berlian Prihatiningrum; Sukanto Sukanto; Dwi Prijatmoko; Leni Rokhma Dewi (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2022)
Insufficient dietary intake in school-age children can result in a weakened immune system, leading to susceptibility to illness. Children will easily be exposed to infectious diseases such as angular cheilitis. Jember has a large population of farmers, categorized as a low-paid occupation. The type of food consumed will affect each person's nutritional status. This study aims to identify the relationship between nutritional status and food intake with the prevalence of angular cheilitis in children grades I–III SDN 7 Nogosari in the agro-industrial setting of Jember. Analytical observation with a cross-sectional design was employed with 58 students as samples, whose nutritional health was assessed using the BMI/U index, visual examination angular cheilitis, and 24-hour recall method of food intake. The SPSS test was undertaken to investigate how variations in macronutrient and micronutrient consumption affect angular cheilitis in each nutritional status. Micronutrient intake that affected angular cheilitis had exceeded the RDA. Furthermore, the SPSS test showed no difference in the consumption of macronutrients and micronutrients in each nutritional status, supporting the occurrence of angular cheilitis at a rate of 0%. In the agro-industrial setting of Kebun Renteng, Jember Regency, students at SD Negeri 7 Nogosari grades I - III had a good nutritional profile with zero percent of angular cheilitis prevalence. It was impossible to determine the association between dietary status and the prevalence of angular cheilitis.